Does Gen-Z have an intention to work in the hotel industry? Empirical study from Indonesia - Situmorang, Ringkar (Emerging Markets : Business and Management Studies Journal, 2024)
The hotel industry focused on the next generation's talent workforce, which would be Generation Z. This study examined the motivation of this generation to work in the hotel industry. Using the TPB (Theory Planned Behavior) framework, researchers deploy a partial least square (PLS) regression to measure their purpose within the industry after graduation. Using data from 239 vocational students from various hotel schools in Greater Jakarta, Indonesia, we examine the positive attitude, negative attitude, subjective norms, and perceived difficulties in the relationship of their intention to work in the hotel industry. We found that positive attitude, negative attitude, and subjective norms showed significant relations to the perceived difficulties. This result provides practical solutions for hotel managers and educational institutions to come up with special management programs to attract more Generation Z to the hotel industry.